Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1752-4571.2008.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical local adaptation of maize landraces along an altitudinal gradient

Abstract: Crop landraces are managed populations that evolve in response to gene flow and selection. Cross-pollination among fields, seed sharing by farmers, and selection by management and environmental conditions play roles in shaping crop characteristics. We used common gardens to explore the local adaptation of maize (Zea mays ssp. mays) landrace populations from Chiapas, Mexico to altitude. We sowed seeds of 21 populations from three altitudinal ranges in two common gardens and measured two characteristics that est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 44 publications
7
109
0
5
Order By: Relevance
“…It may be more likely that alleles adapted in the highlands are slightly deleterious at lower elevation, consistent with empirical findings in reciprocal transplant experiments in Mexico (Mercer et al 2008); in the Appendix we find the rate at which such an allele already present in the Mesoamerican highlands would transit the intervening lowlands and fix in the Andean highlands. The resulting values depend most strongly on the population density, the selection coefficient, and the rate at which seed is transported long distances and replanted.…”
Section: Theoretical Evaluation Of Convergent Evolutionsupporting
confidence: 70%
See 2 more Smart Citations
“…It may be more likely that alleles adapted in the highlands are slightly deleterious at lower elevation, consistent with empirical findings in reciprocal transplant experiments in Mexico (Mercer et al 2008); in the Appendix we find the rate at which such an allele already present in the Mesoamerican highlands would transit the intervening lowlands and fix in the Andean highlands. The resulting values depend most strongly on the population density, the selection coefficient, and the rate at which seed is transported long distances and replanted.…”
Section: Theoretical Evaluation Of Convergent Evolutionsupporting
confidence: 70%
“…Common garden experiments in Mexico reveal that highland maize has successfully adapted to high-elevation conditions (Mercer et al 2008), and phenotypic comparisons between Mesoamerican and South American populations are suggestive of convergent evolution. Maize landraces (open-pollinated traditional varieties) from both populations share a number of phenotypes not found in lowland populations, including dense macrohairs and stem pigmentation (Wellhausen et al 1957;Wilkes 1977), differences in tassel branch and ear husk number (Brewbaker 2015), and a changed biochemical response to UV radiation (Casati and Walbot 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…How these processes may affect a cultivated species like maize, in which the tracking of environmental conditions depends on human decisions and which, from a population genetics perspective, shows a metapopulation structure (21), remains to be studied. Already, however, there is evidence of greater local adaptation of highland than of lowland landraces in southern Mexico, and the former do not seem to express the plasticity necessary to sustain productivity under warming conditions (22). Highland Mexican races, which show introgression with teosinte (Zea mays subspecies mexicana) (23) and have a high genetic diversity among New World maize races (24), may be the most threatened because of their strong local adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal common garden studies with maize have found that highland landraces show higher fitness and seed quality in highland conditions, while lowland landraces have higher fitness in mid-altitude locations (Mercer et al, 2008). Traits such as pigmentation, stem hair, plant height, and flowering time have been shown to be adaptive to altitude, but completely different genes underlie local adaptation to highland conditions in Mesoamerica and South America (Mercer et al, 2008). Field sampling of Mexican teosinte populations helped to clarify that maize adaptation to the Mexican highlands resulted due to introgression from wild teosinte .…”
Section: Human Selectionmentioning
confidence: 99%